DEVELOPMENT OF METHODS FOR ASSESSING THE SAFETY OF LIGHT HYDROCARBON STORAGE FACILITIES IN EMERGENCY SITUATIONS - Permyakov, Vladimir N.; Omelchuk, Mikhail V. (Journal of Applied Engineering Science, 2021)
The risk of accidents involving light hydrocarbons is caused by the physicochemical properties of the components, primarily propane and butane. The most catastrophic accidents involving these substances were on November 19, 1984, in the city of San Juan Ixhuatepec (Mexico) and on June 4, 1989, on the Asha – Ulu-Telyak section (USSR), in each of which more than 500 people died. The novelty of the study is determined by the requirement to ensure industrial and fire safety of storage facilities for light hydrocarbons by predicting probable zones of air flow stagnation. The authors calculated the formation of probable air stagnation zones for various space-planning solutions by using a three-dimensional modelling system and the finite volume method. The paper developed a methodology for assessing the safety of storage facilities for light hydrocarbons in emergency situations, which is based on the analysis of probable air stagnation zones by using three-dimensional modelling systems. The practical significance of the study is determined by the additional development of a parameter for assessing the safety state of a storage facility for light hydrocarbons (Ks) and a resulting parameter (Kr) for calculating the optimal location of structures and their structural changes. Integration of stagnation zone sizes into a single formula with the results of other safety calculations is an urgent scientific and applied problem.
Keywords: air stagnation zones; safety; modelling; computational fluid dynamics; light hydrocarbons